The relationship between customer experience management and business performance in sri lankan printing and publishing industry (colombo region) - Sinhalage Hansini Pramudika; Wickramasooriya, L.H.T.De.S. (University of Jaffna, 2016)
Sri Lankan Printing and Publishing Industry fulfill an essential need of people. Nowadays this industry faces a very serious threat from the digital media.. But unfortunately there is a lack of attention of authorized parties to protect this particular industry.. Implementing management strategies will be able to build a strong foundation for the safe of the industry. Therefore, this research was implemented to measure the relationship between Customer Experience Management and Business Performance in printing and publishing industry. Colombo region was the study area and from the population 35 companies were selected as the sample. Both quantitative and qualitative data were collected by using interview administrated questionnaires. The study disclosed several attractive findings. Even though there is a relationship between Customer Experience Management and Market Performance, there is not a relationship between Customer Experience Management and Financial Performance. So it is somewhat difficult to interpret that there is a relationship between Customer Experience Management and Business Performance or there is not a relationship between Customer Experience Management and Business Performance because. Business performance contains both Market and Financial Performances. From the dimensions in Customer Experience Management, two dimensions (Emotional Customer Experiences & Rational Customer Experiences) have been identified as influenced dimensions to Market Performance. And also this research was found the reasons for not having a relationship between Customer Experience Management and Financial Performance. The influence of Political factors and Economical Factors are directly affected to the Business Performances more than Customer Experience Management strategies when consider their financial Performances.
Keywords: Business performance; Customer experience management; Financial performance; Market performance